Extravagant Expression of Travel and Growth: Grove’s Quest for America - Stich, K. P. (Studies in Canadian Literature, 1981)
F.P. Grove, in his main autobiographical creations A Search for America, Over Prairie Trails, and In Search of Myself, fails to be extravagant enough to achieve a new identity. He methodically manipulates connections between travels in geographical and psychological space, and he is a no less accomplished poseur or trickster in his life as a writer in North America than in his past in Europe. By focusing on metaphors, puns, and related linguistic foregrounding, one can observe Grove’s complex game of hide-and-seek with the reader; that is, one can see that the actualities of Grove’s European past are intricately concealed behind biographical innuendoes and a deceptively simple foregrounding of North American incidents and setting.